Knowledge of Exclusive Breastfeeding Among Adolescent Mothers in Primary Health Tarakan, Nort Kalimantan, Indonesia - Johan, Reza Bintangdari; Noviyanti, Nur Indah; Situmorang, Teresia Suminta Rotua; Mufdlilah, Mufdlilah (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2024)
Breast milk is the primary source of nutrition for infants. However, not all babies receive exclusive breastfeeding. Among adolescent mothers, barriers and challenges in breastfeeding play a significant role in achieving breastfeeding success. This is closely related to the mother's knowledge in overcoming these challenges. The aim of this study was to assess the knowledge of adolescent mothers about exclusive breastfeeding. The study employed an analytical observational method with a cross-sectional study design. A total of 96 adolescent mothers participated in the study, selected using accidental sampling. The research instrument was a questionnaire, and the data were analyzed using the chi-square test. The results showed that the majority of mothers provided exclusive breastfeeding to their babies (55.2%) and had a high level of knowledge (73.6%). There was a significant relationship between mothers' knowledge and exclusive breastfeeding (p = 0.001 < 0.05), with the odds ratio indicating a 0.235 times lower likelihood of not providing exclusive breastfeeding among mothers with higher knowledge. High knowledge among adolescent mothers about exclusive breastfeeding positively influenced the provision of exclusive breastfeeding to their infants. Health education and breastfeeding counseling are essential for adolescent mothers to support and encourage them to continue breastfeeding their babies until the age of 6 months without cessation.